Physicochemical Properties, Heavy Metal Contamination, and Resource Recovery Potential of Petroleum Sludge in Indonesia - Fadilah, Siska Nuri; Setiawan, Wahyu; Setiawan, Pratama; Putri, Aninda; Gulo, Fakhili (Universitas Gadjah Mada, 2026)
Petroleum sludge (PS) is a hazardous waste rich in hydrocarbons and heavy metals, posing significant risks to the environment. Although numerous studies have been conducted globally, a comprehensive characterization of PS originating from Indonesia remains scarce. This study aims to fill this gap by conducting a thorough physicochemical characterization, environmental pollution assessment, and sustainable utilization potential evaluation of PS. The results revealed that the sludge contains a high oil content (15.56%), an extremely high COD level, and is dominated by iron as a heavy metal (4,585.67 mg/L). The TCLP analysis showed that Pb exceeded the regulatory threshold, indicating a significant leaching potential and toxicity risk. BET analysis indicated a mesoporous structure with a specific surface area of 4.73 m2/g, suggesting its potential use as an adsorbent or catalyst support. The high elemental composition of carbon (25.05%), hydrogen (3.10%), and calorific value (3,418 kcal/kg) further highlights its potential for thermochemical conversions such as pyrolysis or gasification. These findings provide a scientific foundation for PS management in Indonesia and highlight its potential conversion into value-added resources, thereby supporting circular economy strategies and sustainable development goals.